Evaluating water projects : cost-benefit analysis versus win-win approach - Johansson, Per-Olov; Kriström, Bengt (SpringerBriefs in economics, 2013)
Should more water be diverted to or from electricity generation? This timely question is addressed in this short volume. Two different approaches are introduced and compared: The first is a cost-benefit analysis, examining the case of re-regulating a Swedish hydropower plant in which water is diverted from electricity generation to the downstream dryway. The proposed scenario generates environmental and other benefits, but comes at a cost in terms of lost electricity. The second study introduces an approach very different from the one used in conventional cost-benefit analysis, and provides a set of measures designed so that most, if not all, affected parties will be better off. Thus, in contrast to a conventional cost-benefit analysis, which draws on hypothetical compensation measures, the new approach envisages actual compensation. Comparing two different theoretical frameworks on the basis of a real-world case, this study can be seen as a manual that can be used to evaluate reasonably small re-regulation of rivers.